Emergency Embolization of Ruptured Giant Renal Angiomyolipoma in a Young Patient with Tuberous Sclerosis - Bozzi, A; Di Martino, A; Raso, A; Ortenzi, M; Rizzotto, A; Chegai, F; Coratella, F (Journal of Endovascular Resuscitation and Trauma Management, 2021)
We present a case report of a young patient with tuberous sclerosis and massive retroperitoneal bleeding from giant renal angiomyolipoma following a car accident. We treated this patient with emergency embolization procedures.